Drug utilization pattern and appropriateness of prescription in IPD geriatric patients in a tertiary care teaching hospital - Pathy, Shuchisuta P.; Pandey, Sachchidanand; Rath, Bhabagrahi; Dash, Rinu Rani (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Drug utilization research provides insights into different aspects of drug use and drug prescribing such as pattern, quality, determinants and outcomes of drug use. Polypharmacy is considered to be hazardous for the elderly, because of their greater vulnerability to drugs and multiple drug use. Prescription of potentially inappropriate medications (PIMs) has been found to be a common cause of morbidity and mortality among the geriatric population and has necessitated the creation of criteria for the safe use of medicines among them. Objectives of the study were to assess the drug utilization pattern in geriatric patients and analyse their prescriptions as per the World Health Organization (WHO) core prescribing indicators and STOPP and START criteria. Methods: An observational, cross-sectional study was conducted from May 2019 to August 2019 in inpatient department of general medicine of VIMSAR, Burla. Prescriptions of ≥65 year patients were collected and documented by active surveillance from the medicine ward. Results: Majority of the patients were in age group of 65-75. Stroke is the more common comorbidities among geriatric population. Average number of medication per prescription is 5.42. About 78.74% of drugs are injectable. The percentage of antibiotics prescribed to patient is 27.75%. Based on STOPP criteria potentially inappropriate medications PIM is 7% and START criteria PIM is 29%. Conclusions: Our study suggests that prevalence of polypharmacy was high which is usually unavoidable in geriatric patients and less PIM is suggestive of adherence to WHO core prescribing indicators, and prescription of drugs as per STOPP and START guidelines are indicative of scope for improvement.